UPAYA KERJA DALAM RANGKA MENINGKATKAN KINERJA PEGAWAI SEKRETARIAT BADAN DIKLAT PERHUBUNGAN DI JAKARTA - Syafek Jamhari (Universitas Negeri Jakarta, 2010)
The main purposes of this research is to identify and acquire the necessary information regarding the work effort in improving employee’s job performance. The research was conducted at Secretariat of Education and Training Agency on Ministry of Transportation in Jakarta, during October 2008 to January 2009. The method is survey with questionnaire as tool for data collecting. This research included 40 employees as unit analysis. Data is analyzed using descriptive approach. The results indicate the employees of Secretariat of Education and Training Agency on Ministry of Transportation in Jakarta have both high work effort and job performance. Based on those findings it could be concluded that high work effort has effected employees’ job performance at Secretariat of Education and Training Agency on Ministry of Transportation in Jakarta. Therefore, the employees job performance should be kept by giving the rewards. It should be put into account in maintaining employees at Secretariat of Education and Training Agency on Ministry of Transportation in Jakarta.